2019
DOI: 10.3390/antiox8020037
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Microwave-Assisted Extraction Process of Bioactive Compounds from Annatto Seeds (Bixa orellana L.)

Abstract: This study deals with the extraction, optimization, and evaluation of the antioxidant and antimicrobial activities of bioactive compounds obtained from the seeds of annatto using microwave-assisted extraction as compared to leaching. Annatto seeds were subjected to a microwave treatment of 2450 MHz and power of 700 watts using a response surface design involving four factors: pH (4–11), solvent concentration (ethanol) (50–96 %), solvent-to-seed ratio (2–10), and microwave exposure time (0–5 min). The contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
2
27
1
Order By: Relevance
“…The previously diluted annatto seed extract (~0.1 g of freeze-dried sample suspended in 30.0 mL of DI water) was again diluted with acetone to obtain an absorbance below 1.0 at 486 nm employing a UV/Vis spectrophotometer (Genesys 10S UV-Vis, Thermo Scientific, Waltham, MA, USA). The mg of bixin per gram of sample was calculated from a calibration curve of bixin standard built between 12.5 mg/L and 0.19 mg/L [37].…”
Section: Quantification Of Bixinmentioning
confidence: 99%
“…The previously diluted annatto seed extract (~0.1 g of freeze-dried sample suspended in 30.0 mL of DI water) was again diluted with acetone to obtain an absorbance below 1.0 at 486 nm employing a UV/Vis spectrophotometer (Genesys 10S UV-Vis, Thermo Scientific, Waltham, MA, USA). The mg of bixin per gram of sample was calculated from a calibration curve of bixin standard built between 12.5 mg/L and 0.19 mg/L [37].…”
Section: Quantification Of Bixinmentioning
confidence: 99%
“…The results showed that the optimal extraction conditions were pH 7.0, solvent concentration 96% v/v, solvent-to-seed ratio 6:1 and microwave time 5 min [42]. The main polyphenols identified in the B. orellana seed extract were apigenin, hypolaetin, and caffeic acid derivatives [42]. Moreover, the B. orellana seed extract isolated by MAE had higher antioxidant activity and polyphenolic yield than that isolated by leaching [42].…”
mentioning
confidence: 98%
“…In addition, isolation of M. communis polyphenolic extract using UAE was more efficient than MAE and conventional solvent extraction methods [41]. In another study, Quiroz et al [42] used MAE to isolate polyphenolic extract from annatto (Bixa orellana L.) seeds. The results showed that the optimal extraction conditions were pH 7.0, solvent concentration 96% v/v, solvent-to-seed ratio 6:1 and microwave time 5 min [42].…”
mentioning
confidence: 99%
See 2 more Smart Citations